PhDing while panicking in a Pandemic - Makama, Refiloe; Peters, Simone (PINS-Psychology in Society, 2023)
The Covid-19 pandemic resulted in a global panic and the destabilisation of economic, and education systems resulting in a sense of anxiety and helplessness at a societal and individual level. We offer a reflection of the end of our PhD journey, that occurred concurrently with the beginning of the Covid-19 lockdown in South Africa. Thinking through an intersectional lens we draw parallels between our precarity as black women in higher education nearing the end of our PhD journey (s) and the unpredictability of life during the pandemic. While we recognise the incompatibility of life during a pandemic and PhDing (completing a PhD), we use this moment to map out how the precariousness in academia lends itself to a sense of anxiety and helplessness often to the death of scholarship. We attribute our panic while PhDing to the process of completing the thesis as well as the sense of insecurity we have observed and experienced within academia. We argue that the casualisation of young black women academics, lends itself to the reproduction of exclusionary practices in higher education.